Erlotinib-related bilateral anterior uveitis. (25th May 2011) - Ali, Kashif; Kumar, Indu; Usman-Saeed, Muniba; Usman Saeed, Muhammad
Abstract : The authors report the case of a 68-year-old woman with secondary adenocarcinoma of the lungs from an unknown primary. Erlotinib was started which produced symptoms suggestive of uveitis. Erlotinib was stopped and restarted a month later at a lower dose, which resulted in severe bilateral anterior uveitis. The uveitis settled after stopping erlotinib and treatment with topical steroids and cycloplegics. To the best of the authors' knowledge, this is the first case of erlotinib-related anterior uveitis.